The legitimacy of the European Union after enlargement - Thomassen, J. J. A. (Oxford University Press, 2009)
In 2004 the European Union was enlarged with ten new member states, eight of them previously communist states in Central and Eastern Europe. This enlargement was without precedent in the history of the Union and its predecessors. It is still to be seen how well the institutions as well as the citizens of the Union are able to cope with the consequences of this operation. The authors of this volume evaluate the effect of that enlargement on its legitimacy. They do so by assessing the effects of enlargement on the functioning of the process of political representation in the European Union and on.